Insurance marketer image construction on the web series “Percaya Ini Cinta” part 1 - Iroth, Yosie William; Putranto, Algooth (Indonesian Journal of Multidisciplinary Science, 2024)
Going beyond their intent of increasing brand awareness, PT Asuransi BRI Life took the initiative to take advantage of the digitalization wave of changes. After the success of the previous Web Series Call Percaya Ini Rindu a couple of years back, BRI Life launches their new Web Series called Percaya Ini Cinta with the ambition to reach the millennial generation to build financial literacy on the importance of financial planning. BRI Life can not avoid the current issues or negative publication of insurance industry which is being criticized or questioned on the professionalism of its sales force and their commitment to pay claims. In order to contribute positively to the industry and to increase the awareness of insurance processes, BRI Life naturally included the construction of the insurance agents in the web series percaya ini cinta. Incorporating the use of language or conversational style of the millennial generation, BRI Life aims to have a positive respond from the audience and seeks to have good reception of the masses. This research aims to see the reception analisis of the audience and to seek how well the reality construction of the insurance agents took place.